Photobiomodulation and orthodontic root resorption: A systematic review and meta-analysis - Jing Yang; Qianqian Zhang; Dehua Zheng; Fengchun Hou (Photodiagnosis and Photodynamic Therapy)
Objectives: Orthodontically induced inflammatory root resorption (OIIRR) is a common adverse effect of orthodontic treatment, characterized by the reduction in root length and volume. Photobiomodulation (PBM), a non-invasive method, has gained attention for its potential in controlling OIIRR. This review aims to analyze and summarize randomized controlled trials (RCTs) to evaluate the impact of PBM on root resorption during orthodontic treatment in humans. Methods: A systematic search was conducted using relevant keywords in the Cochrane Library, PubMed, EMBASE, Web of Science, and ScienceDirect for studies published up to January 2025. Studies were selected based on predefined inclusion and exclusion criteria. The Cochrane Risk of Bias tool (RoB 2) was used to assess the risk of bias in the included RCTs. A meta-analysis was performed using RevMan software (version 5.4), and subgroup analyses were conducted to identify sources of heterogeneity. Results: Eight studies with a total of 185 participants were included in the analysis. The forest plot results demonstrated that LED interventions led to statistically significant improvements in root resorption (MD = –0.15, [95 % CI –0.19, –0.10], p < 0.00001). While LLLT studies indicated a trend toward reduced root resorption, the results did not reach statistical significance (SMD = –1.69, [95 % CI –3.52, 0.14], p = 0.07). The overall change in root length was not statistically significant, except for the canine tooth, where a significant reduction in resorption was observed (MD = –0.49, 95 % CI [–0.95, –0.03], p = 0.04). Subgroup analysis indicated that a wavelength of 850 nm or longer, a fluence exposure greater than 10 J/cm², irradiance less than 25 mW/cm², treatment durations exceeding two minutes, and more than six treatment sessions were associated with a beneficial effect in reducing orthodontically induced inflammatory root resorption. Conclusion: In conclusion, while photobiomodulation (PBM) appears to have a beneficial effect on orthodontically induced root resorption, the current body of evidence is limited, with a low number of studies and considerable heterogeneity. These findings are exploratory and require validation through high-quality trials with robust designs, standardized methods, and longer follow-ups. Registration: PROSPERO registration number - CRD42023444677.